Pengaruh Digitalisasi Platform dan Kontrol Kendali Radio Prambors Terhadap Loyalitas Pendengar - Laili Fithriyah; Salfhaoctha Friemay Aliefia Poetry; Ummy Hanifah; Irfiyah Difa Arwina; Seiza Mawar Al-Hany (Asosiasi Dosen Muda Indonesia, 2026)
The development of digital technology encourages the radio broadcasting industry to adapt through the use of digital platforms and more controlled content management. However, in the midst of increasingly fierce media competition, listener loyalty is a challenge in itself, especially for radio that targets the youth segment such as Radio Prambors. This study aims to analyze the influence of platform digitization and content control on the loyalty of Radio Prambors listeners. The research uses a quantitative approach with an explanatory survey method. Data was collected through an online questionnaire of 100 respondents who were active listeners of Radio Prambors and users of its digital platform. The data analysis technique used multiple linear regression which was equipped with validity, reliability, correlation test, t-test, F test, and determination coefficient. The results show that platform digitization and content control have a positive relationship with listener loyalty, but the effect is relatively weak. Partially, platform digitization and content control show a positive influence on listener loyalty, with content control having a more dominant influence. Simultaneously, both variables were able to explain only a small fraction of the variation in listener loyalty, while most were influenced by other factors outside the research model. These findings show that Radio Prambors' listener loyalty is not only determined by aspects of digitization and content control, but also by the listening experience, program quality, and emotional closeness to listeners.